Genome-wide Meta-analysis Identifies Variants Associated with Platinating Agent Susceptibility Across Populations - Wheeler, Heather E. (2011)
Platinating agents are used in the treatment of many cancers, yet they can induce toxicities and resistance that limit their utility. Using previously published and additional world population panels of diverse ancestry totaling 608 lymphoblastoid cell lines (LCLs), we performed meta-analyses of over 3 million SNPs for both carboplatin- and cisplatin-induced cytotoxicity. The most significant SNP in the carboplatin meta-analysis is located in an intron of NBAS (p = 5.1 × 10(−7)). The most significant SNP in the cisplatin meta-analysis is upstream of KRT16P2 (p = 5.8 × 10(−7)). We also show that cisplatin-susceptibility SNPs are enriched for carboplatin-susceptibility SNPs. Most of the variants that associate with platinum-induced cytotoxicity are polymorphic across multiple world populations; therefore, they could be tested in follow-up studies in diverse clinical populations. Seven genes previously implicated in platinating agent response, including BCL2, GSTM1, GSTT1, ERCC2, and ERCC6 were also implicated in our meta-analyses.